Teacher Competence: Development of Pancasila Education Teaching Materials Based on the Merdeka Curriculum in the Society 5.0 Era - Erna Yuliandari; Moch. Muhtarom; Machmud Al Rasyid Rasyid; Raharjo Raharjo; Pipit Widiatmaka (STAI Hubbulwathan Duri, 2024)
The Merdeka Curriculum mandates teachers to possess specific competencies, particularly in developing teaching materials. However, many teachers struggle to master these competencies, hindering effective curriculum implementation. This study investigates: 1) the competencies MGMP Pancasila Education teachers require in the Society 5.0 era, 2) their proficiency in developing teaching materials aligned with the Merdeka Curriculum at the junior high school level, and 3) the challenges they face in achieving these competencies. This qualitative study employs a descriptive research method, using in-depth interviews, structured observations, and documentation for data collection. Grounded theory analysis is applied to identify patterns and insights regarding teacher competencies and challenges. Findings indicate that competencies needed by MGMP Pancasila Education teachers in the Society 5.0 era include mastering digital technology. However, their ability to develop teaching materials based on the Merdeka Curriculum remains suboptimal, primarily due to difficulties in integrating digital technology into their instructional content. Key obstacles include limited mastery of digital technology competencies and insufficient understanding of the Merdeka Curriculum’s conceptual framework and implementation strategies. These challenges highlight the need for targeted professional development programs to enhance teacher preparedness. This study underscores the critical need for professional training to bridge competency gaps and support teachers in leveraging digital tools to align teaching materials with the Merdeka Curriculum. Addressing these issues is essential for empowering educators to meet the demands of Society 5.0 and achieve curriculum goals effectively.